Female influencers: Analyzing the social media representation of female subjectivity in Italy - Roberti, Geraldina (Frontiers in Sociology, 2022)
The paper addresses the representation of female subjectivity on social media, highlighting how such women's images have a significant impact on the gendered narratives and discourses that populate the public sphere. The article analyzes specifically the pattern of femininity represented by female influencers and the bond they are able to establish with their followers. Starting from the notion of post-feminism sensitivity, it highlights how these celebrities embody its ideals in terms of self-realization, independence and empowerment. Finally, the figures of two of the most popular social media influencers in Italy, Chiara Ferragni and Benedetta Rossi, are analyzed, highlighting their ability to represent a successful model of female digital entrepreneurship. The analysis aims to point out how these media personae provide an ambivalent model of female subjectivity, because on one hand they emphasize women's ability to assert themselves as ambitious, professionally autonomous and free-choosing subjects (as postfeminist culture prescribes), but on the other hand they exploit the spur to female self-fulfillment for marketing aims, turning it into a self-branding tool.